Optimalisasi Pemanfaatan Sistem Informasi Pada UMKM Beladies Laundry Kiloan - Triyadi, Triyadi; Natsir, Fauzan; Anggraeni, Ni Ketut Pertiwi (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
Laundry business is a business that is engaged in laundry services. In the midst of busy activities, laundry is an alternative to washing clothes which is currently being used by many people, especially by urban residents. With so many customers' interest in utilizing the laundry business, laundry business actors have expanded their business by providing kilo washing and dry cleaning services. Utilization of Information and Communication Technology (ICT) is currently growing rapidly so that many business sectors of the community need it to facilitate the operation of their activities, one of which is the laundry business. The Community Service Implementation Team of Universitas Indraprasta PGRI offers an information system based on Rapid Application Development (RAD) that can be used by Beladies Laundry Kiloan business actors to make it easier for business actors and their employees to record transactions so as to minimize data loss that can cause losses. So, there is a need for training in the use of the information system offered so that Beladies Laundry Kiloan employees can optimize the use of the information system.